Modeling Hawaiian Agroecology: Depicting traditional adaptation to the world's most diverse environment - Lincoln, Noa Kekuewa; Haensel, Thomas P.; Lee, Tiffany M. (Frontiers in Sustainable Food Systems, 2023)
Most neglected and underutilized crops were developed and utilized within agroecological cropping systems. Crop suitability must consider the constraints of the environment as well as the conditions of the agroecological system. Using the Hawaiian archipelago as a model system of socioecological dynamics, we consider the distribution of seven agroecological systems and their associated crops to explore how agroecological suitability changes across climate and soils. The seven spatial models of pre-colonial agroecological systems produced extents distributed across much of the Hawaiian archipelago, with clear evolutionary patterns across the archipelago that affect the appropriateness of crop species application.